Daily consumption of functional egg increases hemoglobin level of children with anemia - Gunawan, Delima Citra Dewi; Agus, Ali; Hanif, Muhammad Fathin (Alma Ata University Press, 2024)
Background: Iron is one of the key elements in optimizing the first 1,000 days of life, including stunting prevention. Eggs are animal proteins that are rich in iron and affordable to all, more economically friendly, compared to other animal protein sources like meat.Objectives: This study aims to determine the effect of daily consumption of eggs on height and hemoglobin level of anemic children under five in Yogyakarta.Methods: Double-blind randomized controlled trials were used in the study procedures. The samples included sixteen under-five anemic children, separated into two groups: eight recipients of functional eggs as an intervention group and eight recipients of regular eggs as a placebo group. The intervention was passed during 42 days given continuously1 egg/day in the morning for breakfast.Results: The results showed that there were 1 stunted child in the treatment group and 2 stunted children in the placebo group The average age of recipients was 38 months in treatment and 33 months in placebo. There was an increase in height and hemoglobin with a difference of 1.3 cm for height and 2.8 gr/dl for hemoglobin in the intervention group after being given treatment for 42 days, whereas in the placebo group there was an increase of 0.5 cm for height and 0. 7 gr/dl for hemoglobin. There was a significant difference in hemoglobin levels after the treatment was given between groups (p=0.010), whereas there was not a difference in height (p=0.328). Meanwhile, within intervention group and the placebo group, there were significant differences in height and hemoglobin before and after being given intervention treatment (p<0.05).Conclusions: Daily Consumption of Functional eggs for 42 days can significantly increase hemoglobin levels in children with anemia.